Dietary, Psychological and Lifestyle Factors Associated with Premenstrual Symptoms - AlQuaiz A; Albugami M; Kazi A; Alshobaili F; Habib F; Gold EB (Dove Medical Press, 2022)
AlJohara AlQuaiz,1,2 Muneerah Albugami,3 Ambreen Kazi,1,2 Fahdah Alshobaili,2 Fawzia Habib,1,4 Ellen B Gold5 1Princess Nora Bent Abdullah Chair for Women's Health Research, King Saud University Medical City, Riyadh, Saudi Arabia; 2Department of Family & Community Medicine, King Saud University Medical city, Riyadh, Saudi Arabia; 3Department of Medicine, King Faisal Specialist Hospital and Research Center, Riyadh, Saudi Arabia; 4Department of Gynecology & Obstetrics, Taibah University, Madinah al Munawara, Saudi Arabia; 5Department of Public Health Sciences, University of California Davis, Davis, CA, USACorrespondence: Ambreen Kazi, Princess Nora Bent Abdullah Research chair for Women's Health Research, King Saud University Medical city, PO Box 231831, Riyadh, 11321, Saudi Arabia, Tel +966 1 4692714, Fax +966 1 4691127, Email akamran@ksu.edu.saPurpose: To measure the associations of diet, psycological distress, and lifestyle factors with premenstrual symptoms (PMSx) in women in Riyadh, Saudi Arabia.Patients and Methods: An interview-based, cross-sectional study was conducted on 1831 women aged 18- 50 years seen in primary healthcare centers and teaching institutes in Riyadh from December 2015 to June 2016. Question topics included sociodemographics, physical activity, smoking, and dietary habits information. PMSx were assessed using a symptom checklist with 6 domains: anxiety/mood changes; abdominal/back/joint pain; increased appetite/weight gain, breast pain/tenderness, severe headache, and ≥ 3 PMS symptoms (any). Multivariable logistic regression analyses were conducted to provide adjusted odds ratios (aORs) and 95% confidence intervals (CIs) for factors associated with each PMSx domain.Results: Except for breast pain, drinking > 5 cups of Arabic coffee was associated with increased odds of anxiety/mood [aOR 2.44 (95% CI 1.44, 4.12)], pain [1.83 (1.13, 2.98)], appetite/weight gain [1.66 (1.10, 2.50)], headache [1.57 (1.00, 2.56)] and ≥ 3 symptoms [1.50 (1.07, 2.11)]. A significant association was noted between sugar intake and anxiety/mood symptoms [1.53 (1.07, 2.19)] and abdominal/back pain symptoms [1.84 (1.17, 2.88)]. Increased severity of psychological distress was associated with all symptom domains: anxiety/mood [2.75 (1.92, 3.94)]; pain [1.45 (0.92, 2.28)]; appetite/weight gain [2.01 (1.53, 2.65)]; breast pain [2.19 (1.68, 2.88)]; headache [1.86 (1.37, 2.54)] and ≥ 3 symptoms [3.52 (2.49, 4.95)]. Low physical activity was significantly associated with odds of breast pain symptoms [1.29 (1.04, 1.59)]. Smokers were 3.41 (1.19, 9.77) times as likely to report any ≥ 3 symptoms compared to nonsmokers.Conclusion: Several potentially modifiable factors, such as diet and stress, were positively associated with PMSx. Thus, we suggest that increasing women's awareness of healthy lifestyles, particularly diet and stress reduction, may help to reduce the occurrence of premenstrual symptoms.Keywords: mental distress, coffee, diet, women, premenstrual symptoms